Development of a resonant fatigue testing facility for large-scale beams in bending. (August 2018) - Schneider, Sebastian; Herrmann, Ralf; Marx, Steffen
Highlights: Imbalance rotors were used to generate the forced vibration close to the natural frequency of the tested specimens. A flexible control system was implemented to generate very stable cyclic loading. Higher loading frequencies and hence decreasing test durations could be achieved. Furthermore the reduction in energy costs is enormous. First test results of the new testing facility on railway rail up to 5 ⋅ 10 6 load cycles are presented. Abstract: In this article the development of a resonant bending fatigue test stand for large-scale structural elements at the Institute of Concrete Construction of Leibniz Universität Hannover, Germany, is presented. The aim of the project was to create a controllable forced vibration close to the natural frequency of the tested bending specimens in order to induce fatigue failure in the specimen. By developing a new testing facility and a flexible control system this objective was achieved and initial results of resonant fatigue tests on train rail specimens are presented in this paper. Besides the advantage of the resonant testing system using higher loading frequencies and hence reducing the test duration compared to traditional test stands, the reduction in energy costs is enormous.